CHARACTERISTICS OF RISK FACTORS OF BRONCHIAL ASTHMA IN FERGANA VALLEY (RESULTS OF LONG-TERM EPIDEMIOLOGICAL MONITORING) (World Bulletin of Public Health, 2022)
A literature review analysis is provided in depth and comprehensively, and the effects of the SARS-COV-2 virus on various phenotypes and endotypes of bronchial asthma have been demonstrated. In this regard, it has become urgent to expand epidemiological investigations, but until now, such studies have not been conducted on a large scale, especially in the conditions of Uzbekistan, and in particular, a special pharmacoepidemiological analysis has not been devoted to bronchial asthma, taking into account the conditions of emergency medical care
Keywords: Bronchial asthma; risk factors; characteristics; exacerbation